Rethinking Committee Work in the Research Enterprise: The Case of Regenerative Gatekeeping. Issue 6 (5th November 2022) - Lewis, Jonathan C.; Alemán‐Díaz, Aixa; Behl, Mona; Kolesar, Sarah; White, Lisa; Jones, Brandon; Garza, Corey; Cooper, Sharon
Abstract: Committees touch nearly every facet in the science, technology, engineering, and mathematics research enterprise. However, the role of gatekeeping through committee work has received little attention in Earth and space sciences. We propose a novel concept called, "regenerative gatekeeping" to challenge institutional inertia, cultivate belonging, accessibility, justice, diversity, equity, and inclusion in committee work. Three examples, a hiring committee process, a seminar series innovation, and an awards committee, highlight the need to self‐assess policies and practices, ask critical questions and engage in generative conflict. Rethinking committee work can activate distributed mechanisms needed to promote change. Plain Language Summary: The science, technology, engineering, and mathematics or STEM research enterprise is shaped by the myriad committees that support it, and the committee members making decisions about policies, funding, and personnel effectively serve as gatekeepers. Centering belonging, access, justice, equity, diversity, and inclusion in day‐to‐day committee work can empower many more STEM community members to act as agents of change. We describe a new approach to committee service we refer to as "regenerative gatekeeping" with the aim of broadening participation and improving the climate of geosciences. Key Points: Committee work influences the science, technology, engineering, and mathematics research enterprise Committee members play roles as gatekeepers that maintain the status quo and foster institutional inertia or can become agents of change "Regenerative gatekeeping" provides a framework for promoting belonging, access, justice, equity, diversity, and inclusion